Sistem Informasi Pariwisata Daerah Kabupaten Minahasa Selatan Berbasis Web GIS - Aditya Lapu Kalua; Graciano Emmanuel Martin Pongantung; Deiby Tineke Salaki (Jurnal Ilmiah Sistem Informasi Akuntansi, 2023)
South Minahasa has many tourist attractions, but there is still no place to inform about the tourist attractions in South Minahasa. The Tourism Information System is one of the solutions to provide information to tourists about tourist attractions in South Minahasa. This Tourism Information System for South Minahasa Regency was created to be an information medium for tourists who want to visit tourist attractions in South Minahasa. This information system was created using the RAD (Rapid Application Development) method, this information system uses the Google Maps API to inform the location of tourist attractions, so that tourists can access routes from tourist locations to tourist attractions they want to visit.